2011
DOI: 10.1080/01431161.2010.542204
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructure assessment for disaster management using multi-sensor and multi-temporal remote sensing imagery

Abstract: (2011): Infrastructure assessment for disaster management using multi-sensor and multi-temporal remote sensing imagery, International Journal of Remote Sensing, 32:23,[8575][8576][8577][8578][8579][8580][8581][8582][8583][8584][8585][8586][8587][8588][8589][8590][8591][8592][8593][8594] To link to this article: http://dx.doi.org/10.1080/01431161.2010.542204 PLEASE SCROLL DOWN FOR ARTICLEFull terms and conditions of use: http://www.tandfonline.com/page/terms-andconditions This article may be used for research, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…assess transportation networks. Butenuth et al (2011) used multi-sensor, multi-temporal imagery to identify flooded roads. Ehrlich et al (2009) identified, using pre-and post-disaster very high-resolution (VHR) optical imagery (1m or better), infrastructure and road damage after the 2008 Wenchuan earthquake.…”
Section: Introductionmentioning
confidence: 99%
“…assess transportation networks. Butenuth et al (2011) used multi-sensor, multi-temporal imagery to identify flooded roads. Ehrlich et al (2009) identified, using pre-and post-disaster very high-resolution (VHR) optical imagery (1m or better), infrastructure and road damage after the 2008 Wenchuan earthquake.…”
Section: Introductionmentioning
confidence: 99%
“…Stephenson and Anderson (1997) defined it as a “surveillance technology.” The main advantages of satellite imagery and mapping technology include providing an overview of the impact of large-scale disasters (Matsuoka and Yamazaki, 2004) and facilitating visualization and communication of complex and dynamic information (Prakash and Kulkarin, 2003). From a logistics point of view, Butenuth et al (2011) and Holguín-Veras et al (2012) highlighted the benefits of satellite mapping for assessing damage to critical infrastructures and their accessibility (e.g. the state of the transportation infrastructure), whereas Ichoua (2010) and Roy et al (2012) underlined its role to improve the distribution management of aid to beneficiaries.…”
Section: Satellite Technologies In Disaster Relief Logisticsmentioning
confidence: 99%
“…Many researchers have studied building damage information extraction using multi-source remote sensing data. Butenuth et al (2011) used multi-source remote sensing data to extract road damage information and achieved good results, which indicates its validity in earthquake damage information identification. Chini et al (2012) investigated the inundation and liquefaction resulting from the 2011 Tohoku tsunami through a combination of optical data, thematic maps, and SAR data.…”
Section: Introductionmentioning
confidence: 97%